Laboratory Detection of Female Carriers of Canine Hemophilia - Parks, B. J; Brinkhous, K. M; Harris, P. F; Penick, G. D (Thrombosis and Haemostasis, 1964)
Females known to be heterozygous for canine hemophilia had a plasma antihemophilic factor (AHF, factor VIII) level of about 50%, as determined by bioassay and by the effectiveness of their transfused plasma in raising the AHF levels of hemophilic dogs. Determination of the plasma AHF should serve to identify transmitter females prior to appearance of affected progeny in litters. Lyon’s hypothesis appears to apply to our findings.The simple partial thromboplastin time (PTT) test was prolonged in heterozygous females. Modifications of the test, by the addition of thrombin, a serum accelerator preparation, or kaolin, gave consistently longer PTT values for heterozygotes than for normal dogs. The PTT appears useful as a screening test for carriers of canine hemophilia.